STYLISTICS OF NEMOKKE IN JAVANESE WEDDING CEREMONY IN LANGKAT SUMATERA UTARA - EVA SERVIYANA; MUHAMMAD NATSIR; SISILA FITRIANY LUBIS (LINGUISTICA, 2021)
The research was about Stylistics of Nemokke in Javanese wedding ceremony in Langkat Sumatera Utara. This study was conducted by applying descriptive qualitative design. The source of data was taken from the utterances of dukun manten and activities happened in Nemokke (traditional Javanese wedding ceremony) in Langkat Sumatera Utara. The data are the transcription of the Javanese ‘dukun manten’ utterances recording in Javanese wedding ceremony, especially in Nemokke and activities happened in Nemokke.  The technique for analyzing the data is descriptive qualitative research based on Miles & Huberman (1984). The technique of collecting the data of this research is observation, recording and interview. The findings indicate that there were three Stylistics (Sympson, 2004) found in Javanese wedding ceremony, they were Semantics, Pragmatics and Discourse. It is suggested to the dukun manten in Javanese wedding ceremony to use Discourse to give information and to show the great meaning and audience understand.